Ectopic Varices in Liver Cirrhosis - Lima, Talles Bazeia [UNESP]; Romeiro, Fernando Gomes [UNESP] (Springer Nature, 2020)
Large portosystemic venous collaterals pathways can be found in any part of the gastrointestinal tract, but when these veins are not in the gastroesophageal region they are denominated ectopic varices (EcV). In addition, dilated veins in the abdominal wall and retroperitoneum are also classified as EcV. These veins can cause up to 5% of all variceal bleeding in patients with liver cirrhosis and even more in extrahepatic portal hypertension. When compared with esophageal varices, EcV tend to be larger, leading to significant hemorrhage and requiring more time to find the bleeding source during the endoscopic approach. Despite the advances in diagnostic modalities, the management of EcV is still under debate, requiring skilled doctors on a multidisciplinary team. The initial clinical support for treating gastroesophageal variceal hemorrhage can be extrapolated to EcV bleeding. EcV sites, stigmata of high risk of bleeding, hemodynamic profile, local expertise and resources, the patient’s conditions, and underlying diseases can influence the indication of the therapeutic modality. Endoscopic interventions, such as injection of thrombin, cyanoacrylate, sclerotherapy, and rubber band ligation, should be attempted before radiologic or surgical interventions.
Keywords: Cirrhosis; Ectopic varices; Endoscopy; Gastrointestinal bleeding; Portal hypertension